Role and Responsibilities of the Sharia Supervisory Council (DPS) at Sharia People's Finance Bank (BPRS) in Depok City - Tari, Listari Mauludimah; Habibah Qurrota A'iny; Ifaturochmah; Haritza Hikmatyar; Maisarah (ITQAN: Journal of Islamic Economics, Management, and Finance, 2023)
The aim of this study is to find out how the shariah compliance audit is carried out through the role of the sharia supervisory board (DPS) at PT. BPRS di kota depok.Descriptive qualitative research was used for this project. This study aims to reveal data from natural settings by using the researcher as a key instrument, rather than obtaining the findings through statistical procedures or other computational methods. Descriptive qualitative analysis using inductive method.The responsibility of DPS is not only to submit a report once a semester to Bank Indonesia, but also to be accountable for the nature of the BPRS. When the DPS states that the transaction is prohibited and not in accordance with sharia, the BPRS may not do so. This is the essence of the relationship between BPRS and DPS.The level of DPS credibility in terms of performance, independence, and competence determines the credibility of Islamic banks. The role and function of DPS in sharia internal supervision must be optimized. BI''s main responsibility as a regulator is to improve the external environment of DPS, namely by developing an efficient and effective sharia supervisory mechanism according to sharia.